2010
DOI: 10.1111/j.1538-7836.2010.03885.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Gs hypofunction and abnormal morphology resulting from a heterozygous RGS2 mutation

Abstract: Platelet Gs hypofunction and abnormal morphology resulting from a heterozygous RGS2 mutation. J Thromb Haemost 2010; 8: 1594-603.Summary. Background: Regulator of G-protein signaling (RGS) 2 negatively regulates Gs signaling by inhibiting the activation of adenylyl cyclase (AC). RGS2 mRNA contains four translation initiation sites, leading to four isoforms with different abilities to inhibit AC activity; the largest isoform is the most pronounced inhibitor. A role for RGS2 in platelets is not known. Objective:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…We began by studying the degradation rates of RGS2 translated from four previously identified alternative in-frame initiation sites at methionine 1, 5, 16, and 33 (Met-1, Met-5, Met-16, Met-33) (Fig. 1, A and B) (31,(42)(43)(44) and to explore the role of the N-terminal region. Which of these alternative translation products are expressed endogenously in cells or tissues remains unclear because of low expression, rapid degradation, or limitations of antibodies used for detection.…”
Section: Rgs2 Degradation Requires a Novel N-terminal Bipartite Motifmentioning
confidence: 99%
“…We began by studying the degradation rates of RGS2 translated from four previously identified alternative in-frame initiation sites at methionine 1, 5, 16, and 33 (Met-1, Met-5, Met-16, Met-33) (Fig. 1, A and B) (31,(42)(43)(44) and to explore the role of the N-terminal region. Which of these alternative translation products are expressed endogenously in cells or tissues remains unclear because of low expression, rapid degradation, or limitations of antibodies used for detection.…”
Section: Rgs2 Degradation Requires a Novel N-terminal Bipartite Motifmentioning
confidence: 99%
“…The complex imprinted gene cluster GNAS1 codes Gsα and genetic defects within this cluster (including an extra‐large stimulatory Gsα isoform (XL‐Gsα)) give rise to a range of disorders associated with a thrombotic phenotype and Gsα hyperfunction (data reviewed in [43]). Finally, platelet Gs hypofunction linked to a heterozygous mutation in a regulator of G‐protein signalling (RGS) protein 2 results in different functional RGS2 isoforms with a stronger (and inhibitory) interaction with AC [44].…”
Section: Inherited Variants Of Agonist Receptors and Signaling Pathwaysmentioning
confidence: 99%
“…Although RGS2 has strong selectivity for Gq signaling, it was also shown to regulate Gi and Gs signaling, the latter through a GAP-independent mechanism by directly inhibiting ACs [[32], [33], [34]]. The attenuation of Gs signaling by RGS2 plays a role in platelet formation and signal transduction in olfactory neurons [34,35]; however, the physiological significance of Gs inhibition by RGS2 in metabolism is still largely unknown. Human studies have shown that deregulation of RGS2 is associated with hypertension and susceptibility to metabolic syndrome [36,37].…”
Section: Introductionmentioning
confidence: 99%